Pakistan foreign policy and the legislature - Kizilbash, Hamid H. (Research monograph series - South Asian Institute, University of the Punjab, Lahore ; no. 9., 1976)
Includes excerpts from the speeches of some noted political leaders, delivered in the National Assembly of Pakistan, 1957-1973.